Calcific Uremic Arteriolopathy: A Case Series and Review from an Inner-City Tertiary University Center in End-Stage Renal Disease Patients on Renal Replacement Therapy. (12th February 2021) - Omer, Mohamed; Bhat, Zeenat Yousuf; Fonte, Nanette; Imran, Nashat; Sondheimer, James; Osman‐Malik, Yahya
Abstract : Background and Objectives . Calcific uremic arteriolopathy (CUA) is a rare complication seen, especially in patients undergoing renal replacement therapy (RRT) with high morbidity and mortality. CUA treatment remains challenging. The study evaluated CUA's multifaceted treatment efficacy. Materials and Methods . 24 patients with CUA and on RRT were evaluated at Detroit Medical Center from 2007 to 2016. Skin biopsy was used in almost all patients, along with the radiological and clinical findings. The patient's clinical and paraclinical data were retrieved from the electronic medical records. The effect of treatment modalities and the underlying hyperparathyroidism management were compared to the clinical outcomes using appropriate statistical tests. Results . Twenty-one patients were on hemodialysis, two patients received renal transplants, and one patient was on peritoneal dialysis. Diabetes mellitus was the most prevalent cause of ESRD. The parathyroid hormone level (PTH) was elevated in 22 patients. Fifteen patients were diagnosed 2 weeks or more prior to skin lesion onset. Twenty-two and thirteen patients received sodium thiosulphate and cinacalcet, respectively. Patients with lower PTH and the calcium-phosphate product levels had a relatively better outcome of CUA. Conclusions . A m ultifaceted approach may play a role in treating CUA. Referral to a nephrologist may aid in the early diagnosis and prompt management of CUA.